2016
DOI: 10.1007/s00586-016-4567-4
|View full text |Cite
|
Sign up to set email alerts
|

C5 nerve root palsy following decompression of cervical spine with anterior versus posterior types of procedures in patients with cervical myelopathy

Abstract: Some studies conclude that anterior procedure is more safe. Of all anterior procedures, the multilevel ACDF had the lowest incidence of C5 palsy. The hybrid technique can be chosen for more than two-vertebra corpectomy. In term of posterior procedures, laminectomy is safer. To prevent C5 palsy, electromyography can be used as a sensitive predictor and selective foraminotomy can be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 66 publications
1
16
0
1
Order By: Relevance
“…In our patient cohort, C5 nerve root palsy rate for ACDF only was lowest with 1.13% which is consistent with the literature[ 23 ]. C5 palsy only occurred when segments C4/5 and/or C5/6 were involved in the procedure.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our patient cohort, C5 nerve root palsy rate for ACDF only was lowest with 1.13% which is consistent with the literature[ 23 ]. C5 palsy only occurred when segments C4/5 and/or C5/6 were involved in the procedure.…”
Section: Discussionsupporting
confidence: 92%
“…This observation is in line with the study groups of Bydon and Nassr et al ., who also describe an increasing incidence of C5 palsy after multilevel decompression procedures[ 21 , 22 ]. As the risk of developing a C5 nerve root palsy increased significantly with an increasing number of corpectomies, previous groups suggested the preferential application of a hybrid construct with corpectomy and ACDF whenever possible[ 23 25 ]. We now confirm these suggestions, as the overall incidence of C5 palsy in a combination of ACDF with one-level corpectomy was only 10.7% in our patients compared to 30.3% in two-level corpectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reviews [ 2 , 8 , 15 ] on the prevalence and risk factors of C5 palsy have few included studies or some included studies in the 1990s and 2000s, which was far from now. So, we performed a meta-analysis on incidence of C5 palsy for the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al (9) confronted laminectomy group vs. laminoplasty group reporting a higher incidence in laminectomy group. On the other hand, Basaran et al (10), after a review of the literature, reported a higher incidence in laminoplasty compared to laminectomy, perhaps the highest incidence was found in laminectomy and fusion. The correction of cervical lordotic alignment with posterior instrumentation has been supposed as a contributing factor since able to induce iatrogenic foraminal stenosis and increase the spinal cord shift (11).…”
Section: Discussionmentioning
confidence: 99%